2009
DOI: 10.3109/03630260903344564
|View full text |Cite
|
Sign up to set email alerts
|

Multiplex Ligation-Dependent Probe Amplification Identification of 17 Different β-Globin Gene Deletions (Including Four Novel Mutations) in the Uk Population

Abstract: Large deletions of the beta-globin gene cluster are problematic to diagnose, and consequently the frequency and range of these mutations in the UK is unknown. Here we present a study evaluating the efficacy of the recently available technique of multiplex ligation-dependent prob amplification (MLPA) to determine the range and frequency of these deletions in the UK population. The results revealed a large deletion mutation in 75 of 316 patient samples collected over a 3-year period. Of these, 52 had a common (d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…The deletional mutations were chosen by taking into account ethnic background and according to the published frequencies [10]. Gap-PCR protocols and the primers for the deletional mutations HPFH-1, HPFH-2, HPFH-3, Sicilian (δβ)0-thal, Chinese Gγ(Aγδβ)0-thal, Hb Lepore, Asian-Indian inversion-deletion Gγ(Aγδβ)0-thal, and Turkish inversion-deletion (δβ)0-thal were used as previously described elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The deletional mutations were chosen by taking into account ethnic background and according to the published frequencies [10]. Gap-PCR protocols and the primers for the deletional mutations HPFH-1, HPFH-2, HPFH-3, Sicilian (δβ)0-thal, Chinese Gγ(Aγδβ)0-thal, Hb Lepore, Asian-Indian inversion-deletion Gγ(Aγδβ)0-thal, and Turkish inversion-deletion (δβ)0-thal were used as previously described elsewhere [13].…”
Section: Methodsmentioning
confidence: 99%
“…Despite general carrier frequency for β-globin gene mutations being reported at 2% for Turkey and at as high as 10% for Antalya Province, large deletional mutations in the β-globin gene cluster have rarely been reported so far and there is no systemic study on mutation profiles of large deletional mutations in the β-globin gene cluster in Turkey [4,5,6,7,8,9]. On the other hand, the number of studies on variety and allelic frequencies of large deletions in the β-globin gene cluster has been growing recently [2,3,10,11,12]. Previous studies revealed that HPFH-1, HPFH-2, HPFH-3, Sicilian (δβ)0-thal, Chinese Gγ(Aγδβ)0-thal, Hb Lepore, Asian-Indian inversion-deletion Gγ(Aγδβ)0-thal, and Turkish inversion-deletion (δβ)0-thal mutations are among the most recurrent large deletional mutations in the β-globin gene cluster [10,13].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…We have introduced the MLPA assay in our standard diagnostic routine for those cases that remain negative for mutation detection after gap‐PCR and sequencing analysis. Due to the implementation of MLPA for the detection of deletions and duplications in the α‐ and β‐globin gene clusters, a range of new rearrangements have been identified [Babashah et al, 2009; Gallienne et al, 2009; Harteveld et al, 2005; Lee et al, 2010; Liu et al, 2008; Phylipsen et al, 2010a; So et al, 2009]. However, the exact breakpoints of these deletions remain unknown.…”
Section: Introductionmentioning
confidence: 99%